Maternal chromosome 4 heterodisomy/isodisomy and Bβ chain Trp323X mutation resulting in severe hypodysfibrinogenaemia - Ding, Qiulan; Ouyang, Qi; Xi, Xiaodong; Wang, Xuefeng; Shen, Yiping; Wang, Hongli (Thrombosis and Haemostasis, 2012)
We report a rare case of congenital hypodysfibrinogenaemia due to maternal uniparental disomy of chromosome 4 (mat UPD 4) and a maternally inherited novel nonsense mutation Trp323X in the fibrinogen Bβ chain (FGB) gene. Western blot analysis of patient's plasma revealed an abnormal fibrinogen which consisted of truncated Bβ chain and normal Aα and γ chains. Patient's clinical history and laboratory evidence are presented. Microsatellite genotyping analysis revealed a mixed nature of heterodisomy and isodisomy along chromosome 4. High density SNP genotyping array analysis further confirmed the mat UPD 4 and defined two segments of chromosome 4 (4pter-p15.33 and 4q31.21–4q32.3) as maternal isodisomy (iUPD4) and the remaining regions as maternal heterodisomy (hUPD4), with the FGB gene carrying the mutation resided in the iUPD4 region on the long (q) arm. It was predicted that the segmental nature of iUPD and hUPD was caused by three recombination events at positions around 167.96 cM, 145.51 cM and 14.40 cM on chromosome 4 followed by a meiosis I non-disjunction. This case is clinically and molecularly unique and offers an opportunity for understanding novel mechanisms of congenital hypodysfibrinogenaemia associated with complex UPD and fibrinogen secretion.
Keywords: Fibrinogen / fibrin; haemostasis; gene mutations; thrombosis